2017
DOI: 10.1016/j.rmcr.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy “Shock” with vitiligo due to nivolumab administration as third line therapy in lung adenocarcinoma

Abstract: Non-small cell lung cancer is still diagnosed at late stage due to the lack of early symptoms and methods of diagnostic prevention. In the past ten years several targeted therapies have been introduced or explored. Tyrosine kinase inhibitors and immunotherapy are currently considered the most effective and safe therapies in comparison to the non-specific cytotoxic agents. Regarding tyrosine kinase inhibitors the adverse effects have been fully explored, however; on the other hand for immunotherapy there are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…International Publisher electromagnetic navigation and cone beam ct bronchoscopy [1][2][3]. At advance stage disease we need tissue biopsies for non-small lung cancer patients in order to investigate the expression of a number of genes which are associated with the treatment options of a patient [4][5][6]. In specific we have to investigate the expression of epidermal growth factor (EGFR), anaplastic lymphoma kinase (ALK), proto-oncogene B-Raf (BRAF), proto-oncogene tyrosine-protein kinase-1 (ROS1) and programmed death-ligand-1 (PD-L1).…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…International Publisher electromagnetic navigation and cone beam ct bronchoscopy [1][2][3]. At advance stage disease we need tissue biopsies for non-small lung cancer patients in order to investigate the expression of a number of genes which are associated with the treatment options of a patient [4][5][6]. In specific we have to investigate the expression of epidermal growth factor (EGFR), anaplastic lymphoma kinase (ALK), proto-oncogene B-Raf (BRAF), proto-oncogene tyrosine-protein kinase-1 (ROS1) and programmed death-ligand-1 (PD-L1).…”
Section: Ivyspringmentioning
confidence: 99%
“…The tyrosine kinase inhibitors have pneumonitis, esophagitis and skin rash which is associated in most cases with the dosage [14,15]. Immunotherapy has orogonitis, pneumonitis, athritis, vitiligo, resurgence of hepatitis and disregulation of the thyroid gland [6,16] An aspect that has not been fully investigated is the differences of adverse effects, gender and disease response between chemotherapy and immunotherapy [17][18][19][20][21]. In the current research paper we investigated the differences of adverse effects between chemotherapy and immunotherapy in first line treatment for squamous cell carcinoma.…”
Section: Ivyspringmentioning
confidence: 99%
“…The mean onset delay is 31 weeks, similar to what observed in melanoma patients (Figure 3). In 2017, Zarogoulidis et al reported a case of leukoderma during anti-PD-1 therapy of lung adenocarcinoma [124], and a second case was reported one year later [125] (Figure 3). Leukoderma lesions were also reported in two patients affected by renal cell carcinoma and in patients with cholangiocarcinoma or squamous cell carcinoma [126,127].…”
Section: Melanoma-associated Leukoderma Beyond Melanomamentioning
confidence: 99%
“…In any case it is a very efficient treatment modality. However; immunotherapy in lung cancer has numerous side effects such as tumor necrosis syndrome, vitiligo, psoriasis, acute thyroiditis and hepatitis resuscitation [ [20] , [21] , [22] , [23] ]. Uveitis, pancreatitis, central nervous system disease, and peripheral neuropathies have also been reported [ 24 ].…”
Section: Discussionmentioning
confidence: 99%